FEASIBILITY AND COMPARISON OF NON-INVASIVE HEMODYNAMIC DEVICES IN THE EMERGENCY DEPARTMENT; USCOM VS NICCOMO. Issue 12 (23rd November 2015) - Green, SJ; Hussain, S; Hue, J; Patel, J; Coats, T; Sims, M
Abstract : Objectives & Background: Within emergency medicine there is a demand for non-invasive techniques to measure patient observations. Within resuscitation of unwell patients, measuring Cardiac Output (CO) and Systemic Vascular Resistance (SVR) is carried out in intensive care environment using invasive techniques. In this study we trialled the use of two non-invasive Cardiac Output monitors to assess their feasibility and agreement. The USCOM (USCOM) is a suprasternal Doppler device that uses ultrasound technology and has been extensively researched within clinical medicine. The Niccomo (Medis) device is a novel biothoracic impedance monitor. Methods: Patients were recruited as part of the 'multi-modality monitoring in the emergency department' trial, University Hospital Leicester NHS trust (UHL). Adult patients with a wide range of clinical conditions presenting to the ED who were able to consent were recruited to the study. Devices were attached as per manufacturer instructions, with standard medical care ongoing throughout the study. Data was analysed using R statistical computation. Results: 215 patients were included in the study with an age range 18–95 years. 93 patients had readings for both modalities. Figure 1 represents a Bland-Altman comparing average CO readings of USCOM vs Niccomo with the global average USCOM reading was considerably lower than the Niccomo device. Figure 2, shows SVR of USCOM vs Niccomo, this again highlighted a large difference between measurements. Conclusion: This study revealed the Niccomo measured CO and SVR readings similar to the expected range of patients in this study. However, the USCOM revealed a significantly lower reading for CO and a higher SVR reading than the Niccomo. Further work needs to be undertaken to assess the clinical utility of the different methods to measure cardiac output. The study emphasises that different non-invasive methods of cardiac assessment are not interchangeable.